The Japanese tattoo - Fellman, Sandi (New York, N.Y. Abbeville Press, Inc., 1986)
A collection of photographs of the Irezumi, a secretive group of people drawn from the Japanese underworld who have chosen to have themselves transformed through tattooing into living works of art.
Keywords: Tattooing -- Japan; Tattooing -- Japan -- Pictorial works; Japan -- Social life and customs